Veterinary record open
Veterinary Record Open is a journal dedicated to publishing veterinary research across a range of topic areas including those of a more niche and specialist nature to that considered in the weekly Veterinary Record. Research from all disciplines of veterinary interest will be considered. It is an Open Access journal of the British Veterinary Association.